CORAL COVER, FISH POPULATIONS, AND MANAGEMENT PRACTICES OF MARINE PROTECTED AREAS (MPAS) IN TUBURAN, CEBU - Del Fierro, Esperanza M; Nellas, Angelie C; Jaca, Cristie Ann L; Flores, Marchides F (Journal of Agriculture and Technology Management; Vol 24 No 2 (2021): Vol 24 No 2 (2021): Journal of Agriculture and Technology Management (JATM) Volume 24 July - December 2021 Issue, 2021)
A practical implementation of marine management practices will warrant long-term sustainability of marine protected areas (MPAs) and stability of the fishers' livelihood in the area. This research presents the coral cover, fish diversity and describes the management practices of Barangay Sto. Nino and Barangay Apalan marine protected areas in Tuburan, Cebu, Philippines. Coral reef survey, visual fish census, and MPA Management Effectiveness Assessment Tool (MEAT) are employed. Results showed that the reef in Sto. Niño exhibits a high percentage of live hard corals at 49%, and dead corals with algae and rubble with only 15%. The fish density in the area is 508 individuals/250sqm whereas live hard coral (LHC) cover in Apalan is 24%. A dead coral percentage is relatively high at 38%, and fish density is 349 individuals/250sqm. Massive corals dominated the two MPAs, followed by submassive and branching corals. Both MPAs recorded damselfish (Pomacentridae), wrasse (Labridae), and coral health indicator fishes (CHI), such as butterflyfish (Chaetodontidae), and angelfish (Pomacanthidae). Overall evaluation of the reef conditions of Sto. Niño and Apalan MPAs are "fair" and "poor," respectively. Accordingly, there is a need to periodically prioritize local biological monitoring and MPA evaluation through institutional collaborations (i.e., local government, academe) to imp